Household related predictors of burn injuries in an Iranian population: a case-control study - Sadeghi-Bazargani Homayoun; Arshi Shahnam; Mashoufi Mehrnaz; Deljavan-anvari Reza; Meshkini Mohammad; Mohammadi Reza (BMC, 2012)
Abstract Background To prevent burn injuries it is vital to have sound information on predictors of its occurrence in different settings. Ardabil Province is the coldest province of Iran with high burden of burn injuries. The aim of this study was to determine the household related predictors of unintentional burns in Ardabil Province located at North-West of Iran. Methods The study was conducted through a hospital based case-control design. 239 burn victims as well as 246 hospital-based controls were enrolled. Both bivariate and multivariate analysis methods were used. Results Males comprised 55.2% of all the study subjects. Mean age of the participants was 21.8 years (95% CI: 19.17-24.4). The economic ability of the households was associated with risk of burn injuries. Multivariate conditional logistic regression results showed the following variables to be independent factors associated with burn injuries. Using non-conventional pipe-less air heaters instead of conventional piped kerosene- or gas-burning heaters (Odds ratio: 1.98, 95% CI: 1.1-3.6). Common use of picnic gas-stove for cooking at home (odds ratio = 1.6, 95%CI: 1-2.4). Using electric samovars instead of other types of samovars (Odds ratio = 0.3, 95% CI: 0.1-1). Using samovars lacking the national standard authorization mark (Odds ratio = 2.2, 95% CI: 1.4-3.6). Conclusion Using some types of specific heating or cooking appliances, and unsafe use of conventional appliances were major risk predictors of burn injuries in this population.